The world almanac who's who of film - Aylesworth, Thomas G.; Bowman, John Stewart 1931- (World Almanac, 1987)
"A Bison book." Contains over 2400 biographies of international movie personalities, past and present, arranged alphabetically.
Keywords: Acteurs de cinéma - Biographies - Dictionnaires anglais; Cinéma - Biographies - Dictionnaires anglais; Film; Motion picture actors and actresses -- Biography -- Dictionaries; Motion pictures -- Biography -- Dictionaries; Filmschauspieler; Biografie; Wörterbuch